The significance of endeavour funding scheme by Amanah Ikhtiar Malaysia (AIM) among the small scale entrepreneurs / Mohd Zahid Laton...[et. al.] - Laton, Mohd Zahid; Yunus @ Junor, Harlina; Abd Majid, Azeman; Samsudin, Mawarti Ashik (Universiti Teknologi MARA Cawangan Pahang, 2013)
This study focuses on the Microcredit Scheme borrowers in Pahang, one of the states in the east coast of Malaysia. The study was conducted during an induction course in entrepreneurship jointly organised by the Malaysian Islamic Economic Development Foundation (YAPEIM) and the Pahang state Amanah Ikhtiar Malaysia (AIM). This descriptive research focuses on the participants who were involved in Endeavour Funding Schemes and were asked to complete the microcredit questionnaires while participating in the induction course. The findings are expected to help the microcredit lender in setting the loan amount and the rate of repayment by the borrowers. This presumably helps to ensure the effectiveness and success of the microcredit programmes in the future.